2022
DOI: 10.1111/1751-2980.13118
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of endoscopic ultrasound‐guided gastroenterostomy for gastric outlet obstruction in different sites: A single‐center retrospective study

Abstract: Objectives: Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) has recently been employed as a novel treatment for gastric outlet obstruction (GOO). The aim of this study was to evaluate the safety and efficacy of EUS-GE for GOO at different sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…We also excluded those that did not specify the techniques used or if there were mixed EUS-GE techniques in the pool of patients. A total of 20 studies fulfilled our inclusion criteria: 12 case series and eight comparative studies [12,14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also excluded those that did not specify the techniques used or if there were mixed EUS-GE techniques in the pool of patients. A total of 20 studies fulfilled our inclusion criteria: 12 case series and eight comparative studies [12,14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported AEs [12,14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The rates were 9.3% and 21.4% for DGE and BTGE (Table 6), respectively.…”
Section: Total Adverse Eventsmentioning
confidence: 97%
See 3 more Smart Citations